Physiological limits to endurance exercise performance: influence of sex - Joyner, M. J. (The Journal of Physiology, 2016)
This brief review summarizes factors associated with elite endurance performance, trends in distance running training, and participation by men and more recently women. It is framed in the context of key ideas about the physiological determinants of endurance performance but also touches on some historical and sociological factors relevant to the overall topic. Historical trends that served to increase women's participation in elite endurance events are also discussed as is the role of increased volume and intensity of training. The rapid improvement in women's world record marathon times in the 1970s and 80s are emblematic of these trends and represent a combination of increased training volume and intensity and more competitive opportunities. This occurred as bans on participation by women in endurance events were lifted. For men these same trends evolved over a much longer time frame. The main physiological factor responsible for 10-12% slower times in women compared to men at the elite level are also considered and probably centre around VO2max.